Upaya Peningkatan Kualitas Pendidikan Melalui Program Tematik Posdaya Berbasis Masjid - Sunarto, Andang; Khoirunnisa, Kurnia; Aquaria, Famella; Sari, Mepi Junita; Sari, Vera Puspita; Azzahra, Intan; Suntia, Anggi; Lesiana; Rahmadani, Adika; Khadapi, Muhammad Prayuda (MENYALA: Jurnal Pengabdian Masyarakat, 2024)
Preliminary research indicates that public awareness of the significance of education and the level of public education remain low, supporting the implementation of this service program. Seluma, Sukaraja District, and KKN, which is based at the Al-Muhajirin Mosque, have developed a number of programs aimed at raising the standard of community education service. TPQ teaching and tutoring are running smoothly in the program. The community will continue this program independently.